1996
DOI: 10.1074/jbc.271.46.29049
|View full text |Cite
|
Sign up to set email alerts
|

rek, a Gene Expressed in Retina and Brain, Encodes a Receptor Tyrosine Kinase of the Axl/Tyro3 Family

Abstract: Rek (retina-expressed kinase) has been identified as a putative novel receptor-type tyrosine kinase of the Axl/ Tyro3 family with a potential role in neural cell development. rek clones were isolated from a chick embryonic brain cDNA library with a DNA probe obtained by reverse transcriptase-polymerase chain reaction of mRNA from Mü ller glia-like cells cultured from chick embryonic retina. Sequence analysis indicated that Rek is a protein of 873 amino acids with an extracellular region composed of two immunog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 71 publications
0
32
0
Order By: Relevance
“…Both tyrosine 779 and methionine 782 are conserved in many tyrosine kinases (Hanks et al, 1988) and the corresponding Y1313 of the Met RTK is not involved in association of signaling molecules (Ponzetto et al, 1993). In contrast, Biscardi et al (1996) propose that the corresponding position in the Rek receptor, another member of the Ufo/Axl family, may function as a potential binding site for the p85 subunit of PI3-kinase, especially as a tyrosine 821-like binding site for p85 is not present in this receptor. An interesting article by Stover et al (1995) demonstrated that two tyrosines (Y891 and Y920), located in the kinase domain of the EGF receptor are tyrosine phosphorylated by src and may function as an interaction site for src and p85a, respectively.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Both tyrosine 779 and methionine 782 are conserved in many tyrosine kinases (Hanks et al, 1988) and the corresponding Y1313 of the Met RTK is not involved in association of signaling molecules (Ponzetto et al, 1993). In contrast, Biscardi et al (1996) propose that the corresponding position in the Rek receptor, another member of the Ufo/Axl family, may function as a potential binding site for the p85 subunit of PI3-kinase, especially as a tyrosine 821-like binding site for p85 is not present in this receptor. An interesting article by Stover et al (1995) demonstrated that two tyrosines (Y891 and Y920), located in the kinase domain of the EGF receptor are tyrosine phosphorylated by src and may function as an interaction site for src and p85a, respectively.…”
Section: Discussionmentioning
confidence: 87%
“…Ufo/Axl was identi®ed as the ®rst member of a new family of receptor tyrosine kinases (RTK), comprising at least three members, each of which has several names: Ufo/Axl/Ark/Tyro7, Tyro3/Sky/Rse/Brt/Tif/Dtk/Rek and Nyk/Mer/Eyk/Tyro12 (Janssen et al, 1991;O'Bryan et al, 1991;Rescigno et al, 1991;Lai and Lemke, 1991;Lai et al, 1994;Ohashi et al, 1994;Mark et al, 1994;Fujimoto and Yamamoto, 1994;Dai et al, 1994;Crosier et al, 1994;Biscardi et al, 1996;Paul et al, 1992;Graham et al, 1994;Jia and Hanafusa, 1994). These RTKs are characterized by an unique extracellular structure, resembling neural cell adhesion molecules (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The product of the growth arrest speci®c gene gas6 (Gas6) (Man®oletti et al, 1993) is a growth factor identi®ed as the ligand for Axl/Ufo tyrosine kinase receptors (RTK) (referred thereafter as Axl) (Janssen et al, 1991;O'Bryan et al, 1991;Varnum et al, 1995). Axl is a RTK de®ning a subfamily of RTK with Rse/Sky, c-Mer/Nyk and Rek (Biscardi et al, 1996;Graham et al, 1994;Ling and Kung, 1995;Mark et al, 1994). More recent studies have shown that Gas6 can similarly bind and activate Rse/Sky and Mer RTK, although with lower a nity (Chen et al, 1997;Mark et al, 1996;Nagata et al, 1996;Ohashi et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent sequence analysis revealed that Dtk and Brt were alternative splice variants (Lewis et al, 1996b). The chicken ortholog was cloned in 1996 but was given the name Rek because of limited amino acid sequence identity with the mouse and human genes (66% and 68%, respectively) (Biscardi et al, 1996). While many of these names were used initially in the literature, Tyro-3, Axl, and Mer (or MerTK) have become the most commonly published and will be used exclusively throughout the remainder of this review.…”
Section: A Cloning/nomenclaturementioning
confidence: 99%